The Effect of Health Education on The Knowledge and Adherence of Diet for Gout Arthritis Patients - Aupia, Anatun (Universitas Muhammadiyah Semarang, 2021)
Uric acid is the result of production by the body, so its quality can be normal in the blood and urine. However, the rest of the protein metabolism of foods containing purines also produces uric acid. One variable that impacts uric acid levels is the knowledge a person has so that a better lifestyle can be improved by providing health education. This research purpose is to establish the effect of health education on knowledge and adherence to the gout diet on gout arthritis patient. Pre-experimental with One group pretest-posttest design has been used in this research. Forty-five respondents were collected using total sampling and a questionnaire was used to measure the data. The analysis data using the Wilcoxon Signed Rank Test showed that the significance value (p-value) is about 0.000 <0.05 which indicate that there is an effect of health education on knowledge and adherence. It can be deduced there is an effect of health education on knowledge and adherence to diet for gout arthritis patients.